2011
DOI: 10.1159/000324798
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence Detection of <i>Chlamydia trachomatis</i> by Polymerase Chain Reaction in Endocervical Samples of Infertile Women Attending University Hospital in Manaus-Amazonas, Brazil

Abstract: Background: We established for the first time the prevalence of Chlamydia trachomatis infection among infertile women in Manaus Amazonas Brazil using the polymerase chain reaction (PCR) technique. Methods: 106 women were studied at a public university hospital fertility clinic for infertility problems correlated with chlamydia infection. Social-economic and clinical information was obtained before medical examination to obtain samples for the amplification of C. trachomatis DNA plasmid. Results: The prevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
5
2
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 37 publications
(24 reference statements)
5
5
2
2
Order By: Relevance
“…Similar detection rates of C. trachomatis in infertile patients by PCR have been reported in previous studies from developing countries . Studies show that chlamydial infections cause more damage to women's reproductive health than to men's . In the present study too, C. trachomatis was detected more in women (15.7%) than in men (10.0%) Furthermore, C. trachomatis was detected in 20.0% of infertile couples suggesting the need for routine screening of C. trachomatis infection in all infertile couples.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar detection rates of C. trachomatis in infertile patients by PCR have been reported in previous studies from developing countries . Studies show that chlamydial infections cause more damage to women's reproductive health than to men's . In the present study too, C. trachomatis was detected more in women (15.7%) than in men (10.0%) Furthermore, C. trachomatis was detected in 20.0% of infertile couples suggesting the need for routine screening of C. trachomatis infection in all infertile couples.…”
Section: Discussionsupporting
confidence: 89%
“…This suggests that young women are the most at risk for Chlamydia and confirms that these individuals are an important target for health education interventions to encourage behavioural changes. Previous studies have shown that diagnosing C. trachomatis infections in women is difficult since, most infections are asymptomatic (13,14). However, in the present study, vaginal discharge, lower abdominal pain, irregular menstruations were significantly associated with C. trachomatis infection in infertile women.…”
Section: Discussioncontrasting
confidence: 54%
“…Entre pacientes de uma clínica de reprodução em São Paulo, houve 1,1% de prevalência de CT. A baixa prevalência observada foi justificada devido aos tratamentos prévios prescritos para DST para as pacientes inclusas nesse estudo 5 . Contudo, observou-se 52,8% de infecção por CT em pacientes na clínica de reprodução em Manaus devido à inclusão de pacientes com fator tubário 16 .…”
Section: Discussionunclassified
“…A escassez de estudos sobre esse tema no Brasil, particularmente com mulheres inférteis, se deve a vários fatores, principalmente à falta de sintomas clínicos, que dificulta a identificação das mulheres infectadas 5,16 . Há dificuldade de acesso a testes laboratoriais para detecção dos patógenos por reação em cadeia da polimerase (PCR), sobretudo nos serviços de saúde públicos.…”
Section: Introductionunclassified
“…C. trachomatis incidence in different studies has ranged from 52.8% when tested by PCR of endocervical samples from subfertile women in Brazil (de Lima Freitas et al., ) to as low as 1.0% in a population of asymptomatic subfertile women in Germany by PCR of urine samples (Eggert‐Kruse et al., ). In male partners, C. trachomatis infection has ranged from 39.4% in Tunisia when detected by PCR in semen and first‐void urine samples (Gdoura et al., ) to 0.304% in a Canadian cohort study where both urine and semen samples were tested (Domes et al., ).…”
Section: Introductionmentioning
confidence: 99%